2017
DOI: 10.26582/k.49.2.6
|View full text |Cite
|
Sign up to set email alerts
|

The foot posture index between elite athletic and sedentary college students

Abstract: Abstract:Sports participation may lead to musculoskeletal adaptation and alter foot posture; however, the effect of high impact sports on foot posture has not fully been understood yet. The purpose of this study was to investigate the difference in foot posture between elite collegiate athletes participating in high impact sports and sedentary college students using the Foot Posture Index (FPI). Foot postures of 30 elite collegiate athletes of high impact sports and 30 sedentary controls were observed in stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…The foot posture assessment is common in clinical practice for injury prevention and intervention. In population without ID, the participation in sports have been associated with a more pronated foot posture [7]. Additionally, flatter and more pronated foot posture has been observed in some of the previous studies in obese individuals [8], [9].…”
Section: Introductionmentioning
confidence: 74%
“…The foot posture assessment is common in clinical practice for injury prevention and intervention. In population without ID, the participation in sports have been associated with a more pronated foot posture [7]. Additionally, flatter and more pronated foot posture has been observed in some of the previous studies in obese individuals [8], [9].…”
Section: Introductionmentioning
confidence: 74%
“…Wojtys et al [28] reported negative effects caused by intensive training begun at early ages on the structure of the foot, whereas Aydog et al [27] stated that intensive training of gymnasts from early ages on had no negative effects on the structure of their foot and associated this with the exercises that strengthen and flex the muscles in the foot. Similarly, Kuo and Liu [31] stated that there was no age-related variation in the structure of the foot.…”
Section: Discussionmentioning
confidence: 98%
“…Such type of foot posture would be understandable considering that after weight acceptance, the foot slowly moves 6 BioMed Research International 7 BioMed Research International into pronation and attains maximum pronation in midstance. In this position, the midtarsal joint unlocks, and the foot stretches and becomes more flexible to accommodate the underlying surfaces that help to assist in maintaining balance [31].…”
Section: Discussionmentioning
confidence: 99%